2005
DOI: 10.1111/j.1525-139x.2005.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

American Society of Diagnostic and Interventional Nephrology Section Editor: Stephen Ash: Stenosis Surveillance of Hemodialysis Grafts by Duplex Ultrasound Reduces Hospitalizations and Cost of Care

Abstract: Most recent randomized controlled trials (RCTs) have found that hemodialysis graft surveillance combined with preemptive correction of stenosis does not prolong graft survival. Nevertheless, such programs may be justified if they reduce other adverse outcomes or decrease the cost of care. This study tested this hypothesis by applying a secondary analysis to our original RCT. This study of 101 patients evaluated correction of stenosis based upon blood flow (Q) and stenosis surveillance. Patients were randomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Furthermore, although access survival was no different in members of the group who underwent surveillance, it is possible that their lower incidence of thrombosis may translate into a reduction in access-related costs and hospitalizations, as demonstrated in a reanalysis of a small study by Dossabhoy et al 80 and by a quality improvement project conducted by Wijnen et al 81 In the latter study, flow surveillance produced a 32.5% reduction in the overall cost of access care. Savings occurred chiefly in the prosthetic access group and resulted from reduction in the number of invasive procedures, central catheters, and hospitalizations.…”
Section: Evidencementioning
confidence: 94%
“…Furthermore, although access survival was no different in members of the group who underwent surveillance, it is possible that their lower incidence of thrombosis may translate into a reduction in access-related costs and hospitalizations, as demonstrated in a reanalysis of a small study by Dossabhoy et al 80 and by a quality improvement project conducted by Wijnen et al 81 In the latter study, flow surveillance produced a 32.5% reduction in the overall cost of access care. Savings occurred chiefly in the prosthetic access group and resulted from reduction in the number of invasive procedures, central catheters, and hospitalizations.…”
Section: Evidencementioning
confidence: 94%
“…20 There is evidence that stenosis surveillance by DUS combined with preemptive correction, regardless of other criteria, may be superior to an invasive strategy based only on clinical or flow criteria. 21 Two recent clinical trials reported different results using DUS screening followed by PTA in prosthetic grafts for HD access. Malik et al 7 showed significantly longer prosthetic graft patency with DUS performed every 3 months, whereas Robbin et al 8 reported no significant decrease of graft failure rates or thrombosis with DUS performed every 4 months.…”
Section: A B Cmentioning
confidence: 99%
“…Research has shown that regular surveillance may lead to improved quality of life for dialysis patients, 15) possibly from a reduction in the quantity of time spent in hospitals due to complications of access failure. 16) This benefit, however, has to be viewed in the context of unnecessarily exposing patients to increased numbers of salvage interventions as a consequence of routine surveillance. 17,18) Importantly, there is substantial evidence that regular surveillance of AVGs may not decrease the risk of graft thrombosis, 19) nor prolong the time to graft abandonement.…”
Section: )mentioning
confidence: 99%